Dr. Anthony Okeregbe and Dr. Serawit Debele - Okeregbe, Anthony; Debele, Serawit B. (Cluster Conversations, 2023)
Cluster fellow Dr. Anthony Okeregbe talks with his host Dr. Serawit Debele, leader of the Cluster's Junior Research Group on Intersectionality, about his recent project entitled "The Child’s Right to ‘Sex’: Negotiating Sexuality Pedagogies in Entangled Moral Spaces".